Perbandingan Sensitivitas Metode RT-PCR Dan Rapid Antigen Test Terhadap Deteksi Dini Infeksi Covid-19 Pada Tenaga Kesehatan - Sekarwati (CV. SINAR HOWUHOWU, 2025)
This study aims to compare the sensitivity of RT-PCR and rapid antigen tests in the early detection of COVID-19 infection among healthcare workers, a high-risk occupational group. The research employed a cross-sectional design involving healthcare workers from various clinical units. Each participant underwent both rapid antigen and RT-PCR testing using nasopharyngeal specimens. The results show that RT-PCR maintains the highest sensitivity, particularly in individuals with low viral loads. In contrast, rapid antigen tests exhibit lower sensitivity, with a significant decrease in samples with Ct values > 30. However, rapid antigen tests demonstrate high sensitivity in cases with high viral load (Ct ≤ 25), making them useful for rapid initial screening. This study concludes that rapid antigen tests can serve as early detection tools, but RT-PCR confirmation is essential to ensure diagnostic accuracy, especially among asymptomatic or high-risk healthcare workers.